Emotional intelligence and level of pospandemic physical activity in university students in Lima - Aquino LLanos, Janeth Paola (2024)
The research carried out analyzes the relationship between emotional intelligence and the level of physical activity of university students at a public university in Lima. Study with a quantitative, descriptive, non-experimental correlational cross-sectional approach. The sample was intentional or by convenience and was made up of 138 students from the last two years of the Faculty of Education. To collect the data, two international scales were used: “Trait Meta-Mood Scale (TMMS-24)” to measure emotional intelligence and “international physical activity test IPAQ”. The results indicate that men have 53.8 % 53.8 % EI classified as low 30.2 % moderate, the accumulated being 84%, 16% classified as high. While women 61.3 % of I.E classify as low, 32.3 % moderate, the accumulated is 93.5 %, with only 6.5 % classifying high, as for the levels of physical activity, those with the greatest sedentary lifestyle are students from 18 to 20 years old with 50 %, followed by those from 24 to 27 years old with 41.4%, those from 21 to 23 years old with 39.7 % and those from 27 to 32 years old with 14.3 %. In the analysis of the Spearman correlation coefficient between both variables, the result is 0.100 and has a p-value (bilateral) of 0.245, so the null hypothesis was accepted.